2017
DOI: 10.1007/s00705-017-3636-2
|View full text |Cite
|
Sign up to set email alerts
|

Feline immudeficiency virus subtypes B and A in cats from São Luis, Maranhão, Brazil

Abstract: Feline immunodeficiency virus (FIV) is a retrovirus of the genus Lentivirus that is distributed worldwide, with prevalence rates varying between 2.5% and 44%. FIV causes immunosuppression, with depletion of TCD4 lymphocytes, with the majority of clinical signs caused by secondary and opportunistic infections. Blood samples were collected from nine domestic cats (Felis catus domesticus) from the city of São Luís, Maranhão State, Brazil. All samples were positive in a rapid immunochromatographic test (SNAP® Comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Subtype D has Zealand. Recombinant sequences were also found among the subtypes, which occurred between A-B, B-D, and A-C (Samman et al, 2011;Perhari c et al, 2016;Zhang et al, 2017;Martins et al, 2018).…”
Section: Discussionmentioning
confidence: 97%
“…Subtype D has Zealand. Recombinant sequences were also found among the subtypes, which occurred between A-B, B-D, and A-C (Samman et al, 2011;Perhari c et al, 2016;Zhang et al, 2017;Martins et al, 2018).…”
Section: Discussionmentioning
confidence: 97%
“…Here, the reported prevalence estimates range from 2–37.5%. Preliminary studies suggested that FIV infection is widespread in the domestic cat population of Brazil, predominantly with subtype B, with a single report of subtype A circulation in cats in Maranhão, north-eastern Brazil, 5,2124 but little is known about the prevalence and phylogeny of FIV in most states in the northeast region of Brazil. 5,25 Finally, a better characterization of FIV strains circulating within Brazil is required to augment our understanding of the significance of FIV in felids in this country.…”
Section: Introductionmentioning
confidence: 99%
“…FIV clade A strains are found worldwide [16,25,26,27,28]; the other clades show varying geographic prevalence, and the separate evolution of these clades in geographical distinct areas [14,29] and introduction into other areas has been proposed [15,26,30,31,32,33]. The most prevalent FIV clades found in Europe are A and B, with clade A being predominant in Northern Europe (Germany, Benelux, and the UK) [16,32,34,35,36] and clade B occurring more frequently in Southern Europe (Portugal, Italy, Austria, Croatia, and Turkey) [16,20,24,29,34,37].…”
Section: Introductionmentioning
confidence: 99%
“…In North America, FIV clades A, B, and C have been described [15,16,31,33]. In South America, clades A, B, and E have been reported, with clades B and E being predominant and clade E only being described in this geographic area so far [18,28,38,39,40,41]. Limited information on the FIV strains and clades is available for Asia.…”
Section: Introductionmentioning
confidence: 99%